Preliminary bioassays to evaluate the toxicity of lindano on Simocephalus vetulus (O.F.Muller, 1776) (Crustacea: Cladocera) - Juárez, Jorgelina (2007)
Lindano is known by its toxicity and its capacity of bioacumulation in organisms, becoming a material dangerous for the human health and the environment. The objective of the present work was to evaluate the acute toxicity of the lindane on the cladoceran Simocephalus vetulus . Cultures were made in camera of incubation in conditions controlled with average differentials (seaweed and in- fusorians). The bioensayos were implemented with a control, 5 dilutions and 3 retorts. The value of CL50 to 48 hours of exhibition as opposed to the different concentrations from lindane was of 11,4 μg/l, which refl ects the greater sensitivity of the organism proves in relation to other antecedents.